Preparation, Characterization, Electronic Structures and Non-linear Optical Properties of Some Asymmetrical Schiff Base Compounds as Model Compounds for Non-Linear Optical Organic Materials - Sheikhshoaie, Iran (Asian Journal of Chemistry, 2016)
Three mono azo asymmetrical bidentate Schiff base compounds (1–3) were synthesized and their structures characterized by some spectroscopic methods and C, H and N elemental analyses. Also some theoretical calculations about the electronic properties of the structures of synthesized compounds have been performed. The theoretical non-linear optical properties (b values) of these compounds were calculated with AM1 semi-empirical method by using MOPAC 7.0 program package and the electronic analysis of the electron density distribution was used to explain an increase of the molecular hyperpolarizabilities.